A study on the production systems of Pacific Paint and Oil Manufacturing Incorporated - Ayes, Sheryl V. (College of Engineering, 2002)
Pacific Paint & Oil Manufacturing Inc., (PPOMI), is the leading manufacturer of paint products in the country. It is best known for its products under the trademark name Boysen, which constitutes 70% of its annual production volume. Beside Boysen paints, it also manufactures Nation and Coat Master brand paints. The former covers the 30% of the production while the latter contributes to the remaining 10%. TO have an edge among its competitors, the company focuses on the following competitive priorities: low cost, consistent quality and on time delivery. A Production and Operations Management study was conducted in PPOMI. Basic area of interest include Capacity Planning, Inventory Management and Supply Chain Management were covered & discussed in the paper. A streamline diagnosis diagram was used to identify the 3 major problem areas in the company. The problems identified are inaccurate forecasting technique used, high ideal stock level set by the company and insufficient capacity. The current forecasting method used by PPOMI is a 20% mark-up from the previous year's sales with this method, there is a significant deviation from the actual demand. The study group considered the exponential smoothing method with five different smoothing constants as an alternative. After the evaluation of alternatives based on the different forecast performance measures & reduction in the total inventory costs, the exponential smoothing parameter with a=0.2 outperforms the other methods used. The ideal stock level set by the company results to very high capital tied up in inventory. The study group suggested that PPOMI employs the p-system to come up with the best amount of finished goods inventory. With this proposal, a significant decrease in the total inventory costs and months of supply were observed. Under the capacity planning, the present capacity (in machine hours) of each workstation was documented. Output capacity measures were used in the computing for the capacity because the company was a variety of product mix. The utilization was also computed. Filling machines show a high percentage utilization rate. Hence, the estimated number of machines that should be present on the filling section was computed. Results show that there is a capacity gap of 1 machine in the filling section. A cost comparison of the present capacity and its capacity if it will buy another machine showed that the company would benefit if there is an additional filling machine. The savings is approximately 79,000 per month. Areas for further study include the effect of production of paints in the vicinity of the company. Pollution and noise issues are said to be a problem in the area. However, the group did not consider this in the paper. During the visits, the said problems were not apparent. Also, the ineffective cross-functional relationship between the production department and the marketing department should be further studied by the Human Resource (HR) personnel. The said problem is beyond the scope of IE 151.